Cobalt chemistry for smooth topology

By screening bath additives and specific electroplating compositions by cyclic voltammetry, the problems of differences in sediment smoothness and thickness during cobalt electroplating are solved, high-quality cobalt deposits are achieved, and the performance of electrical interconnects is improved.

CN114761620BActive Publication Date: 2025-01-10MACDERMID ENTHONE INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202080083568.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-13
Filing Date
2020-12-08
Publication Date
2025-01-10
Estimated Expiration
2040-12-08

AI Technical Summary

Technical Problem

The prior art is difficult to achieve defect-free and smooth cobalt deposits during cobalt electroplating, especially in submicron-sized characteristic areas, and it is difficult to minimize the variation in the cover thickness between the characteristic and non-characterized areas, resulting in electrical The interconnects are of poor quality.

Method used

Cyclic voltammetry is used to screen cobalt electroplating bath additives, combined with cobalt ion source, boric acid, pH regulator and organic additives (such as inhibitors), and electroplating under specific conditions to achieve smooth topology of cobalt deposits and thickness difference of less than 200nm , reduce impurities and joints.

Benefits of technology

The cobalt deposit without voids and joints on the semiconductor substrate is achieved, reducing the variation in the thickness of the cover layer between the characteristic and non-featured regions, and improving the quality and reliability of the electrical interconnects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114761620B_ABST
    Figure CN114761620B_ABST
Patent Text Reader

Abstract

The present invention discloses an electroplated cobalt deposit and a method for electrodepositing cobalt on a surface to produce a flat deposit on a substrate surface. The cobalt electrolyte contains (1) a cobalt ion source; (2) boric acid; (3) a pH adjuster; and (4) an organic additive, which contains an inhibitor. The electroplated cobalt deposit exhibits a flat surface such that the thickness difference across substantially the entire surface of the substrate is less than about 200 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The compositions and processes described herein are generally directed to electrolytic deposition chemistries and methods for depositing cobalt and cobalt alloys. These compositions and methods are used for cobalt-based metallization of interconnect features in semiconductor substrates. Screening methods for identifying suitable bath additives are also described. Background Art

[0002] In the damascene process, electrical interconnects are formed in an integrated circuit substrate by metal filling of interconnect features (such as vias and trenches) formed in the substrate. Copper is a preferred conductor for electronic circuits. Unfortunately, when copper is deposited on a silicon substrate, it can diffuse rapidly into the substrate and dielectric films (such as SiO2 or low-k dielectrics). Copper also has a tendency to migrate from one location to another when current passes through an interconnect feature in operation, thereby creating gaps and hillocks. Copper can also diffuse into device layers that are built on top of a substrate in a multilayer device application. Such diffusion may be detrimental to the device because it may damage adjacent interconnects and / or cause leakage between two interconnects. Leakage may result in an electrical short circuit, and the corresponding diffusion outside the interconnect feature may interrupt the current.

[0003] As the size of electronic devices decreases and the performance expectations increase, the need for defect-free and low-resistivity interconnects in the electronic packaging industry has become urgent. As the density of integrated circuits within microelectronic devices continues to increase with each generation or node, interconnects become smaller and their aspect ratios generally increase. The build-up process using barrier and seed layers prior to Damascus copper plating currently has disadvantages that are becoming more and more apparent as the demand for higher aspect ratio features and higher quality electronic devices increases. Therefore, a plating chemistry that is more suitable for achieving defect-free metallization is needed.

[0004] When filling submicron vias and trenches by electrolytic deposition of copper, it is usually necessary to first deposit a barrier layer on the wall of the cavity to prevent copper from diffusing and electromigrating into the surrounding silicon or dielectric structure. In order to establish a cathode for electrodeposition, a seed layer is deposited above the barrier layer. The barrier layer and seed layer can be very thin, especially when the plating solution contains appropriate formulations of promoters, inhibitors and levelers. However, as the density of electronic circuits continues to increase and the inlet size of through holes and trenches becomes smaller and smaller, even very thin barrier layers and seed layers will gradually occupy a higher proportion of the inlet size. When the aperture reaches a size below 50nm, especially less than 40nm, 30nm, 20nm, or even less than 10nm (8 or 9nm), it becomes increasingly difficult to fill the cavity with a copper deposit that is completely free of gaps and seams. The most advanced features have a bottom width of only 2-3nm, a middle width of about 4nm, and a depth of 100 to 200nm, thereby converting to a depth-to-width ratio between about 25:1 and about 50:1.

[0005] Electrolytic deposition of cobalt is performed in a variety of applications in microelectronic device manufacturing. For example, cobalt is used in the overlay of Damascus copper metallization used to form electrical interconnects in integrated circuit substrates. However, due to the higher resistivity of cobalt deposits, such processes have not previously provided satisfactory copper electrodeposition alternatives in filling through holes or trenches to provide primary interconnect structures. In a typical semiconductor process, a chemical mechanical polishing / planarization (CMP) step is performed after electrodeposition to polish away the plated deposit or overlay. Rough or uneven surfaces can cause CMP defects, so the smooth topology of the overlay is critical. In addition, rough or uneven surfaces may be particularly problematic due to the difference in overlay (OB) thickness between feature areas and non-feature areas, which is typically expected due to momentum plating. This difference in overlay thickness can be further enhanced with the density of features.

[0006] U.S. Patent Publication No. 2016 / 0273117 filed by Doubina, the subject matter of which is incorporated herein by reference in its entirety, describes a method and apparatus for electroplating cobalt on a substrate, wherein the electroplating may occur by a bottom-up mechanism. Doubina uses various plating additives, including specific combinations of promoters and inhibitors and specific conductivity, to achieve the desired plating effect. However, Doubina does not mention the desire to minimize the variation in overburden thickness between feature and non-feature areas of the substrate, nor does it describe any method for evaluating the effectiveness of bath additives in a cobalt electrolyte to achieve the desired results.

[0007] U.S. Patent Publication No. 2009 / 0188805 to Moffat et al., the subject matter of which is incorporated herein by reference in its entirety, describes a method of electrodepositing at least one ferromagnetic material, which may be nickel, cobalt, or iron, into a three-dimensional pattern within a substrate. Moffat describes controlling the potential between an electrode and a counter electrode, but does not describe any method for evaluating the effectiveness of a bath additive.

[0008] U.S. Patent Publication No. 2019 / 0010624, filed by Commander et al., describes a composition and a method of using such a composition to electrodeposit cobalt onto a semiconductor substrate structure including submicron-sized electrical interconnect features, the subject matter of which is incorporated herein by reference in its entirety. The interconnect features are metallized by contacting the semiconductor base structure with a cobalt electrolytic composition, and an electric current is supplied to the electrolytic composition to deposit cobalt onto the substrate structure and fill the submicron-sized features with cobalt.

[0009] U.S. Patent Publication No. 2019 / 0093248, filed by Josell et al., describes superconformal filling of recessed features with superconformal deposited gold, the subject matter of which is incorporated herein by reference in its entirety. However, the process proposed by Josell is for so-called "currency metals" of gold, silver, and copper, which use additives that are very different from cobalt plating baths. Although Josell describes electrochemical measurements, Josell does not mention the desire to minimize the variation in the thickness of the overburden between feature and non-feature areas of the substrate, nor does he consider how to evaluate the effectiveness of various bath additives.

[0010] Thus, it can be seen that it would be desirable to provide a method of evaluating bath additives for cobalt plating baths to produce desired results.

[0011] To this end, the inventors of the present invention have surprisingly discovered that cyclic voltammetry can be used to analyze and / or screen additives for cobalt electroplating compositions and identify additives that produce suitable / desirable results.

[0012] Cyclic voltammetry can be used to study the qualitative information of electrochemical processes under various conditions and determine the electron stoichiometry of the system, the diffusion coefficient of the analyte, and the formal reduction potential, which can be used as an identification tool. In addition, CV can be used to determine the concentration of an unknown solution by generating a calibration curve of current versus concentration.

[0013] Cyclic voltammetry (CV) is a potentiodynamic electrochemical measurement method that can be used to probe reactions involving electron transfer. In a cyclic voltammetry experiment, the working electrode potential is increased linearly with time during the cycling phase. During the initial forward scan (from t0 to t1), a gradually decreasing potential is applied. Therefore, assuming that a reducible analyte is present in the system, the cathodic current will increase during this time, at least initially. At some point after the reduction potential of the analyte is reached, the cathodic current will decrease as the concentration of the reducible analyte is depleted. If the redox couple is reversible, then reoxidation of the reduced analyte will begin during the reverse scan (from t1 to t2), producing a current of opposite polarity to the previous one (the anodic current). The more reversible the redox couple is, the more similar the shapes of the oxidation peak and the reduction peak will be. Therefore, cyclic voltammetry can provide information about the redox potential and the rate of the electrochemical reaction.

[0014] During each of these phases, the rate at which the voltage changes with time is called the scan rate (V / s) of the experiment. The potential is measured between the working electrode and the reference electrode, while the current is measured between the working electrode and the counter electrode. These data are plotted as a graph of current (i) versus applied potential (E, often simply referred to as "potential").

[0015] After reaching the set potential in the CV experiment, the potential of the working electrode decreases in the opposite direction back to the initial potential. These potential ramp cycles can be repeated as many times as needed. Summary of the invention

[0016] It is an object of the present invention to provide a cobalt deposit which exhibits a smooth topology of the overlying layer.

[0017] Another object of the present invention is to minimize the variation in the thickness of the cover layer between feature areas and non-feature areas.

[0018] Another object of the present invention is to provide a void-free cobalt deposit.

[0019] Another object of the present invention is to minimize impurities in the cobalt electrodeposit.

[0020] It is another object of the present invention to provide a screening method to evaluate the effectiveness of various bath additives for cobalt electroplating baths.

[0021] To this end, in one embodiment, the present invention is generally directed to an electroplated cobalt deposit on a surface of a substrate, wherein the electroplated cobalt deposit exhibits a thickness difference of less than about 200 nm across substantially the entire surface of the substrate.

[0022] In another embodiment, the present invention is generally directed to a method of electrodepositing cobalt onto a substrate comprising recessed features and non-feature regions, wherein the cobalt deposit exhibits a thickness difference of less than about 200 nm over substantially the entire surface of the substrate; the method comprising:

[0023] a) receiving a substrate in an electroplating chamber;

[0024] b) immersing the substrate in a cobalt electrolyte comprising:

[0025] (1) a cobalt ion source;

[0026] (2) Boric acid;

[0027] (3) pH adjusters; and

[0028] (4) an organic additive, wherein the organic additive comprises an inhibitor; and

[0029] c) electroplating cobalt into the features and on the non-feature areas under conditions and for a period of time to achieve level, seamless, bottom-up fill in the recessed features and plating on the non-feature areas. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Cyclic voltammetry curves of Comparative Example 1, Comparative Example 2 and Comparative Example 3 according to the present invention are depicted.

[0031] Figure 2 A photograph of the cobalt deposit described in Comparative Example 1 is depicted.

[0032] Figure 3 A photograph of the cobalt deposit described in Example 2 is depicted.

[0033] Figure 4 A photograph of the cobalt deposit described in Example 3 is depicted. DETAILED DESCRIPTION

[0034] As used herein, "a," "an," and "the" refer to both the singular and the plural, unless the context clearly indicates otherwise.

[0035] As used herein, the term "about" refers to a measurable value, such as a parameter, amount, duration, etc., and is intended to include variations of + / -15% or less, preferably + / -10% or less, more preferably + / -5% or less, even more preferably + / -1% or less, and still more preferably + / -0.1% or less relative to the specifically stated value, as long as such variations are suitable for performing in the invention described herein. In addition, it should also be understood that the value to which the modifier "about" refers is itself specifically disclosed herein.

[0036] As used herein, for ease of description, spatially relative terms such as "below," "beneath," "lower," "above," "upper," etc. are used to describe the relationship of one element or feature structure to another or more elements or features, as shown in the figures. It should also be understood that the terms "front" and "rear" are not intended to be limiting and are intended to be interchangeable where appropriate.

[0037] As used herein, the terms “includes and / or comprises” specify the presence of stated features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or groups thereof.

[0038] As used herein, if not otherwise defined herein for a particular element or compound, the term "substantially free" or "substantially free" means that the given element or compound cannot be detected by ordinary analytical means of bath analysis well known to those skilled in the art of metal plating. Such methods typically include atomic absorption spectroscopy, titration, UV-visible analysis, secondary ion mass spectrometry, and other commonly used analytical methods.

[0039] In one embodiment, the present invention generally relates to an electroplated cobalt deposit on a surface of a substrate, wherein the electroplated cobalt deposit exhibits a thickness difference of less than about 200 nm across substantially the entire surface of the substrate.

[0040] In another embodiment, the present invention is generally directed to a method of electrodepositing cobalt onto a substrate comprising recessed features and non-feature regions, wherein the cobalt deposit exhibits a thickness difference of less than about 200 nm over substantially the entire surface of the substrate; the method comprising:

[0041] a) receiving a substrate in an electroplating chamber;

[0042] b) immersing the substrate in a cobalt electrolyte comprising:

[0043] (1) a cobalt ion source;

[0044] (2) Boric acid;

[0045] (3) pH adjusters; and

[0046] (4) an organic additive, wherein the organic additive comprises an inhibitor; and

[0047] (5) optionally, one or more additional bath additives; and

[0048] c) electroplating cobalt into the features and on the non-feature areas under conditions and for a period of time to achieve level, seamless, bottom-up fill in the recessed features and plating on the non-feature areas.

[0049] The source of cobalt ions may be selected from the group consisting of cobalt sulfate, cobalt chloride, chloroammonium sulfate, and combinations of one or more of the foregoing. In one embodiment, the source of cobalt ions comprises cobalt sulfate heptahydrate.

[0050] In a preferred embodiment, the cobalt electroplating composition is at least substantially free of other metal ions, which means that the content of other metal ions is less than about 1% by weight, more preferably less than 0.1% by weight, and most preferably less than about 0.01% by weight. Most preferably, the cobalt electroplating composition does not contain any metal ions other than cobalt ions.

[0051] Based on this, the cobalt electroplating composition is preferably at least substantially free of copper ions. Although it may be difficult to avoid trace amounts of copper contamination, it is particularly preferred that the copper ion content of the bath does not exceed 20 ppb, for example, in the range of 0.1 ppb to 20 ppb. In the composition defined herein, "substantially free of copper ions" means that there are less than 20 ppb of copper ions in the solution.

[0052] The cobalt ion concentration in the electroplating solution is generally in the range of about 1 g / L to about 50 g / L, preferably about 2 g / L to about 25 g / L, more preferably about 2 g / L to about 10 g / L, and more preferably about 2 g / L to about 5 g / L.

[0053] The electrolytic cobalt composition also optionally but preferably comprises a buffer to stabilize the pH. A preferred buffer is boric acid (H3BO3), which can be incorporated into the composition at a concentration between about 5 and about 50 g / L, preferably between about 15 and about 40 g / L. The pH of the composition is preferably maintained in the range of about 0.5 to about 8. In one embodiment, the pH of the cobalt composition is preferably maintained in the range of less than 5, more preferably in the range of about 1 to about 5, more preferably in the range of about 2 to about 4.5, and most preferably in the range of about 2.5 to about 4.

[0054] The composition includes one or more inhibitor compounds. In one embodiment, the one or more inhibitor compounds include an alkynol compound or a derivative thereof as further described herein. The concentration of the inhibitor is preferably between about 1 mg / L and about 500 mg / L, and more preferably between about 5 mg / L and about 200 mg / L, more preferably between about 1 mg / L and about 70 mg / L, and most preferably between about 20 mg / L and about 50 mg / L.

[0055] The composition may optionally include one or more uniformity enhancing compounds, which preferably include amino polyol compounds or derivatives thereof. Preferred uniformity enhancing agents are ethoxylated, propoxylated triisopropanolamine. In one embodiment, the uniformity enhancing agent has a molecular weight of about 5000 g / mol. Other preferred uniformity enhancing compounds include ethoxylated, propoxylated ethylenediamine, ethoxylated, propoxylated diethylenetriamine and ethoxylated, propoxylated triethylenetetramine. If used, the concentration of the uniformity enhancing agent is preferably between about 10 mg / L and about 4000 mg / L, and more preferably between about 100 mg / L and about 2000 mg / L, and most preferably between about 250 mg / L and about 1000 mg / L.

[0056] Said composition can also optionally comprise one or more depolarizing compounds. One or more depolarizing compounds comprise terminal unsaturated compounds or derivatives thereof, which can depolarize the plating potential. In one embodiment, the depolarizing compound can be selected from sodium propargyl sulfonate, butynedioic acid, acrylic acid, propiolic acid, vinyl phosphonate and mixtures thereof. A preferred depolarizing compound is sodium propargyl sulfonate. If used, the concentration of the depolarizing compound is preferably between about 0.1 mg / L and about 5000 mg / L, and more preferably between about 10 mg / L and about 1000 mg / L, and most preferably between about 100 mg / L and about 500 mg / L.

[0057] In one embodiment, the cobalt electrolyte composition is substantially free of chloride ions, meaning that the chloride content is less than about 1 ppm, more preferably less than 0.1 ppm.

[0058] The electroplating composition also preferably does not contain any 2+ ) is reduced to metallic cobalt (Co 0 ) of any functional concentration of the reducing agent. "Functional concentration" refers to any concentration of the reducing agent that is effective in reducing cobalt ions in the absence of an electrolytic current or is activated by the electrolytic field to react with cobalt ions.

[0059] Additionally, the electroplating composition is preferably at least substantially free of dispersed particles, meaning that there are no or little to no dispersed macroscopic particulate solids in solution that could adversely affect the metal electroplating process.

[0060] In another preferred embodiment, the cobalt composition further optionally but preferably comprises one or more leveling agents, one or more accelerators and / or one or more wetting agents. In other preferred embodiments, the cobalt composition does not comprise and preferably is at least substantially free of accelerators or depolarizers. In other preferred embodiments, the cobalt composition does not comprise and preferably is at least substantially free of leveling agents.

[0061] When divalent sulfur compounds are excluded from the plating bath, the sulfur content of the cobalt deposit is reduced, providing beneficial effects on chemical mechanical polishing and circuit performance.

[0062] The electrolytic composition is substantially free of divalent sulfur compounds if the concentration of divalent sulfur in the plating solution is no greater than 1 mg / l. Preferably, the concentration of compounds containing divalent sulfur atoms is no greater than 0.1 mg / l. Still more preferably, the concentration of divalent sulfur atoms is below the detection level using analytical techniques commonly used by those skilled in the art of metal plating.

[0063] To reduce internal stress in the cobalt deposit, the electrolytic composition may include a stress reliever, such as saccharin. When used, saccharin is present in the electrolytic composition at a concentration between about 10 and about 300 ppm, more preferably between about 100 and about 200 ppm.

[0064] When the plating bath contains an inhibitor and optional uniformity enhancer as described herein, the superfill process can be performed satisfactorily without the need for an accelerator. The inhibitors of the present invention help drive current into these features to allow for efficient bottom-up filling, and the uniformity enhancer helps improve deposit uniformity. The composition is substantially free of a reducing agent that converts Co 2+ Reduction to Co 0 , reducing divalent sulfur, copper ions, nickel ions and iron ions.

[0065] It has also been discovered that certain depolarizing compounds can work in conjunction with the suppressor compounds described herein. These compounds depolarize the plating potential to effectively plate interconnect features.

[0066] In one embodiment, the inhibitor is an acetylenic inhibitor. The acetylenic inhibitor preferably comprises an alkoxylated propargyl alcohol or a reaction product of propargyl alcohol and a second component. Examples of suitable acetylenic inhibitors include, but are not limited to, an alkoxylated propargyl alcohol or a reaction product of propargyl alcohol and glycidol, propylene oxide, glycidol and propylene oxide, or propylene glycol and glycidol. In one embodiment, the alkoxylated propargyl alcohol is an ethoxylated propargyl alcohol. However, it is also contemplated that other alkoxylated propargyl alcohols will also be used in the compositions described herein. Examples of initiators and reactive materials for preparing acetylenic inhibitors according to the present invention are shown in Table 1 below.

[0067] Table 1. Initiators and reactants used to prepare acetylenic inhibitors

[0068]

[0069]

[0070] In one embodiment, x and y are between 0 and 20, more preferably between 0 and 10. In another preferred embodiment, one of x or y is at least 1. Examples of preferred ratios include, but are not limited to:

[0071] x is 0, y is 1-3;

[0072] y is 0 and x is 1-7; and

[0073] x is 1-4 and y is 1-4.

[0074] Other ratios of x and y are also known to those skilled in the art and can be applied to the present invention.

[0075] Table 2 describes several examples of preferred acetylenic inhibitors according to the present invention and formulated using the initiators and reactants described herein.

[0076] Table 2. Preferred specific acetylenic inhibitors

[0077]

[0078] In one embodiment, n is between 0 and 20, more preferably between 0 and 10, most preferably between 1 and 7.

[0079] The electrolytic composition described herein can be used in a method for filling submicron features of semiconductor substrate structures. The submicron electrical interconnect features have a bottom, sidewalls and a top opening. The submicron features include cavities in the substrate structure that are superfilled by rapid bottom-up deposition of cobalt. For example, a metallized substrate including a seed (seminal) conductive layer is formed on the inner surface of the submicron feature by physical vapor deposition of a metal seed layer (preferably a cobalt metal seed layer) or deposition of a thin conductive polymer layer. The metallized substrate is applied to the bottom and sidewalls, and is generally applied to the area surrounding the feature. The metallized substrate in the feature is contacted with the electrolytic composition, and an electric current is provided to the electrolytic composition to cause the electrodeposition of cobalt, thereby filling the submicron feature. A vertical polarization gradient is formed in the feature by the combined action of an inhibitor, an optional uniformity enhancer and an optional depolarizing compound, wherein the growth rate in the vertical direction is greater than the growth rate in the horizontal direction by bottom-up deposition to fill, thereby obtaining a cobalt interconnect that is substantially free of voids and other defects.

[0080] Bottom-up filling means that the deposit grows upward from the bottom of a feature (such as a trench). Bottom-up filling can be classified as V or U-shaped. V-shaped has a sharper bottom from the bottom up, and U-shaped has a flatter bottom from the bottom up. U-shaped bottom-up filling is preferred because V-shaped bottom-up filling can produce seams. Conformal filling means that the deposit grows from the sidewalls and bottom of the feature to the center. The most challenging features usually have a very large aspect ratio (aspect ratio is the ratio of depth to width), and conformal filling usually produces a seam at the center of such features. Depending on the filling mechanism, the seam can be fuzzy or clear. However, after annealing, any seam can produce a seam gap or a center gap.

[0081] "Substantially free of voids" means that at least 95% of the plated features or holes are free of voids. Preferably, at least 98% of the plated features or holes are free of voids, and most preferably, all of the plated features or holes are free of voids.

[0082] "Substantially seamless" means that at least 95% of the plated features or holes are seamless. Preferably, at least 98% of the plated features or holes are seamless, and most preferably, all of the plated features or holes are seamless.

[0083] To implement the electrodeposition method, an electrolytic circuit is formed including a metallized substrate, an anode, an aqueous electrolytic composition, and a power source having a positive terminal in conductive communication with the anode and a negative terminal in conductive communication with the metallized substrate. Preferably, the metallized substrate is immersed in the electrolytic composition. An electrolytic current is delivered from the power source to the electrolytic composition in the circuit, thereby depositing cobalt on the metallized substrate.

[0084] The electrodeposition process is preferably carried out at a bath temperature of about 5°C to about 80°C, more preferably about 20°C to about 50°C, and most preferably room temperature, and at a current of about 0.01 mA / cm 2 to about 20mA / cm 2 between 0.3 mA / cm 2 to about 10mA / cm 2 The deposition is carried out at a current density in the range between . Optionally, the current may be pulsed, which may provide improvements in the uniformity of the deposit. On / off pulses and reverse pulses may be used.

[0085] Typically, the electroplating bath is stirred during use. Any suitable stirring method can be used with the processes described herein, including sparging with air or an inert gas, stirring of the workpiece, impact, etc. In addition, the workpiece can be rotated in the electroplating solution. Alternatively, instead of immersing the workpiece in the electroplating solution, the workpiece can be contacted with the electroplating solution by pumping, spraying, or other means known to those skilled in the art.

[0086] The present invention also generally relates to a screening method for evaluating the suitability of a bath additive for a cobalt electroplating composition.

[0087] As mentioned above, rough or uneven surfaces can cause defects in chemical mechanical polishing (CMP), so it is critical for the overburden to have a smooth topology. In addition, rough or uneven surfaces can be particularly problematic due to differences in overburden (OB) thickness between feature and non-feature areas, which is typically expected due to momentum plating. This difference in overburden thickness can be further enhanced, in part, depending on the density of features.

[0088] It would therefore be desirable to have a reliable screening method for evaluating potential cobalt electroplating compositions and additives contained therein to determine their suitability for producing cobalt deposits having minimal variation in overburden thickness between feature and non-feature areas of a substrate.

[0089] As described herein, the inventors of the present invention have surprisingly discovered that cyclic voltammetry can be used to evaluate cobalt electroplating compositions containing various bath additives. The present invention contemplates an electrochemical screening method for evaluating cobalt electroplating compositions using cyclic voltammetry.

[0090] In the cyclic voltammetry scan, the forward scan represents the non-featured area of ​​the plating, and the reverse scan represents the feature area of ​​the plating. The potential difference between the forward scan and the reverse scan is called the "hysteresis loop" here. A larger hysteresis loop means a larger potential difference, and vice versa. In addition, the size of the hysteresis loop will change with the current density.

[0091] The inventors of the present invention have discovered that a cobalt electroplating composition that exhibits a small hysteresis loop at high current density has a positive effect on the overburden morphology. The hysteresis loop of OB at high current density (typically at least about 5 mA / cm 2 ) will have a negative impact on the OB topology. The inventors of the present invention have found that there is a clear correlation between the hysteresis loop and the OB topology at high current density. It has been found that a larger hysteresis loop will lead to a larger difference in OB thickness between feature areas and non-feature areas, which will lead to defects in CMP and is therefore not preferred for CMP.

[0092] In one embodiment, the hysteresis loop at high current density is less than 50 mV, preferably less than 40 mV, more preferably less than 30 mV, more preferably less than 20 mV, and most preferably less than 10 mV. High current density refers to a current density of at least about 5 mA / cm 2 In the range of about 5 mA / cm 2 to about 10mA / cm 2 More preferably, about 7.5 mA / cm 2 to about 8.5mA / cm 2 The range is preferably about 8 mA / cm 2 In one embodiment, it is desirable to have a current of about 8 mA / cm 2 The hysteresis loop at a current density of is less than about 50 mV, preferably less than about 40 mV, and more preferably less than about 30 mV.

[0093] It has also been observed that at low current density, most of the chemistries with good gap filling performance have a hysteresis loop, although there is no clear correlation suggesting that a larger hysteresis loop may lead to better gap filling.

[0094] It is highly desirable that the variation of the thickness of the cover layer between the feature area and the non-feature area. In one embodiment, the variation of the thickness of the cover layer is controlled to be less than 50nm, more preferably less than 40nm, or less than 35nm, or less than 30nm, or less than 20nm, or less than 10nm.

[0095] Table 3. Hysteresis loop and overlay thickness differences

[0096]

[0097] Plating experiment :

[0098] Temperature - Room temperature

[0099] Waveform :

[0100] 0.5-2mA / cm2 The time required for OCP to complete via filling after ramping current; then 8mA / cm 2 The time required to obtain the desired cover thickness.

[0101] Comparative Example 1 :

[0102] Preparation of 2.95g / L Co 2+ ions, 30 g / L boric acid and sulfuric acid to adjust the pH to 2.75. Ethoxylated propargyl alcohol (40 mg / L) and an amine polyol of about MW 5000 (50 mg / L) were also added to the composition.

[0103] Substrates with submicron features are placed in the bath and charged at 0.5-8 mA / cm 2 Electroplating was performed to provide a seamless fill with a covering layer. Cyclic voltammetry scans were performed using the above waveforms to measure the hysteresis loop.

[0104] Table 3 describes the OB thickness difference (uniformity) and CV hysteresis loop measurements, and Table 4 summarizes the film impurities.

[0105] Example 2

[0106] Preparation of 2.95g / L Co 2+ ions, 30 g / L boric acid and sulfuric acid to adjust the pH to 2.75. Compound I (see Table 2, x=3.6) was added to the bath at a concentration of 240 mg / L.

[0107] Substrates with submicron features are placed in the bath and charged at 0.5-8 mA / cm 2 Electroplating was performed to provide a seamless fill with a covering layer. Cyclic voltammetry scans were performed using the above waveforms to measure the hysteresis loop.

[0108] Table 3 describes the OB thickness difference (uniformity) and CV hysteresis loop measurements, and Table 4 summarizes the film impurities.

[0109] Example 3

[0110] Preparation of 2.95g / L Co 2+ ions, 30 g / L boric acid and sulfuric acid to adjust the pH to 2.75. Compound III (see Table 2, x=3.6 and y=1) was added to the bath at a concentration of 240 mg / L.

[0111] Substrates with submicron features are placed in the bath and charged at 0.5-8 mA / cm 2Electroplating was performed to provide a seamless fill with a covering layer. Cyclic voltammetry scans were performed using the above waveforms to measure the hysteresis loop.

[0112] Table 3 describes the OB thickness difference (uniformity) and CV hysteresis loop measurements, and Table 4 summarizes the film impurities.

[0113] Figure 1 Depicted are cyclic voltammetry (CV) scans of Comparative Example 1, Comparative Example 2, and Comparative Example 3 at 2 mV / s at a speed of 100 rpm from +10 mV vs. OCP to -2 V vs. RE.

[0114] Table 4. Film impurities in the examples

[0115]

[0116] like Figure 1 As shown in Table 3, the hysteresis loop is the potential difference between the forward scan and the reverse scan at the same current density. At low current density, the hysteresis loop represents the gap filling ability; and at high current density, the hysteresis loop represents the performance of OB isolated-dense uniformity. Table 3 summarizes Figure 1 The hysteresis loop of the middle curve. It should be noted that 2mA / cm 2 Indicates low current density, and 8mA / cm 2 The table indicates high current density.

[0117] In addition, in Table 3, the last column summarizes the OB thickness difference between the feature area and the non-feature area using the internal test structure described in this article. This internal test structure is called "454". The feature area of ​​the test structure has grooves with 0.1 micron openings with a spacing of 0.1 micron and is considered a dense feature. The non-feature area is the area next to the feature area. The OB thickness difference can represent the OB isolated-dense uniformity performance. A smaller difference indicates better OB isolated-dense uniformity performance. It can be clearly seen from Table 3 that Comparative Example 1 has a better performance at 8mA / cm 2 The large hysteresis loop is shown at 8 mA / cm 2 Compared with Examples 2 and 3, which have a small hysteresis loop, there is a larger OB thickness difference.

[0118] It is believed that the hysteresis loop at low current density can represent the gap filling ability. In other words, two chemicals with similar hysteresis loops at low current density should be able to provide similar gap filling performance. It can be clearly seen from Table 3 that Comparative Example 1, Example 2 and Example 3 have similar gap filling performance at a low current density of 2 mA / cm 2 All of them have similar hysteresis loops, and it is observed that they have similar gap-filling performance in TEM or STEM.

[0119] The idea of ​​the hysteresis loop theory is to use a chemistry with a large hysteresis loop at low current density and a small hysteresis loop at high current density to achieve both good gap filling and OB isolated-dense uniformity.

[0120] Table 4 summarizes the SIMS data and shows the impurity levels in the deposit. The goal of this study was to reduce the impurities in the deposit as much as possible. Ideally, just the same as VMS or less. In the unique molecular structure of Example 2, it can have much less impurities than other chemistries, and it can still provide adequate gap filling performance.

[0121] Based on this, it can be seen that at 8mA / cm 2 In the case where the OB is plated, a smaller hysteresis loop can result in a smaller difference in OB thickness between the feature area and the non-feature area.

[0122] This observation can also be supported by theory. The feature area requires momentum plating. This means that the feature area has a faster sediment growth rate than the non-feature area. Due to the newer sediment surface, the adsorbed acetylenic inhibitor on the feature area surface is also expected to be less than the acetylenic inhibitor adsorbed on the non-feature area. In the forward scanning part, the potential is scanned from low to high, and in the reverse scanning part, the potential is scanned from high to low. Therefore, during the forward scanning, it is expected that a newer deposition surface will be formed. Therefore, in the CV scan, the forward scan represents the non-feature area plating, and the reverse scan represents the feature area plating.

[0123] In the CV curve, at the same current density, when the forward scan is more cathodic than the reverse scan, this indicates that more energy is required to grow on the non-feature area than on the feature area. In other words, the growth of the deposit on the feature area is enhanced, which may lead to the difference in deposit thickness between the feature area and the non-feature area. This is the fundamental reason why minimizing the hysteresis loop at the OB plating current density is crucial to reducing the difference in deposit thickness between the feature area and the non-feature area.

[0124] Thus, it can be seen that the invention described herein provides improved methods and compositions for cobalt-based metallization of interconnect features in semiconductor substrates. In addition, the invention described herein provides a screening method for evaluating and identifying suitable bath additives to achieve desired results.

[0125] Finally, it is to be understood that the following claims are intended to cover all generic and specific features of the invention described herein, together with all statements of the scope of the invention which might literally fall between them.

Claims

1. An electroplated cobalt deposit on a substrate surface, wherein the electroplated cobalt deposit on the substrate surface comprises submicron recessed features and non-feature areas, and the electroplated cobalt deposit exhibits level, seamless, bottom-up filling in the submicron recessed features and plating on the non-feature areas, wherein the variation in the thickness of the overburden between the submicron recessed features and the non-feature areas is less than 50 nm, wherein at 5 mA / cm 2 Up to 10mA / cm 2 The electroplated cobalt deposit exhibits a potentiodynamic hysteresis loop of less than 50 mV at high current density in a cyclic voltammetry scan at a current density within a range of 1 mA / cm 2 To less than 5mA / cm 2 At current densities within the range of , the electroplated cobalt deposit exhibits a potentiodynamic hysteresis loop of less than 90 mV at low current densities in a cyclic voltammetry scan, wherein the electroplated cobalt deposit is formed by immersing the substrate in a cobalt electrolyte comprising: (1) a cobalt ion source; (2) Boric acid; (3) pH adjusters; and (4) an organic additive, wherein the organic additive comprises an alkoxylated propargyl alcohol or a reaction product of propargyl alcohol and a second component, wherein the second component comprises glycidol, propylene oxide, glycidol and propylene oxide, or propylene glycol and glycidol; wherein the cobalt electrolyte contains less than 1 ppm of chloride ions; wherein the cobalt electrolyte contains an amount of promoter that is undetectable by atomic absorption spectroscopy; and The cobalt electrolyte contains less than 0.1 mg / L of divalent sulfur compounds.

2. The electroplated cobalt deposit of claim 1, wherein at 5 mA / cm 2 Up to 10mA / cm 2 At current densities within the range, the hysteresis loop of the potentiodynamic measurement was less than 30 mV at high current density in the cyclic voltammetry scan.

3. The electroplated cobalt deposit of claim 2, wherein at 5 mA / cm 2 Up to 10mA / cm 2 At current densities within a range of 100 Å, the hysteresis loop of the potentiodynamic measurement was less than 20 mV at high current density in the cyclic voltammetry scan.

4. The electroplated cobalt deposit of claim 3, wherein at 5 mA / cm 2 Up to 10mA / cm 2 At current densities within a range of 100 Å, the hysteresis loop of the potentiodynamic measurement was less than 10 mV at high current density in the cyclic voltammetry scan.

5. The electroplated cobalt deposit of claim 1, wherein the current density of the hysteresis loop of the potentiodynamic measurement at high current density is 7.5 mA / cm 2 Up to 8.5mA / cm 2 or the current density of the hysteresis loop of the potentiodynamic measurement at high current density is 8 mA / cm 2 .

6. The electroplated cobalt deposit of claim 1, wherein the current density of the hysteresis loop of the potentiodynamic measurement at low current density is between 1.5 mA / cm 2 Up to 2.5mA / cm 2 within the range.

7. The electroplated cobalt deposit of claim 6, wherein: At 7.5 mA / cm 2 Up to 8.5mA / cm 2 At current densities within the range of 200 Å to 400 Å, the electroplated cobalt deposit exhibited a potentiodynamic hysteresis loop of less than 50 mV at high current density in the cyclic voltammetry scan.

8. The electroplated cobalt deposit of claim 1, wherein in the cyclic voltammetry scan, a forward scan represents non-feature area plating and a reverse scan represents feature area plating of the electroplated cobalt deposit.

9. The electroplated cobalt deposit of claim 1 wherein the cobalt electrolyte contains a depolarizing agent in an amount not detectable by atomic absorption spectroscopy.

10. A method of electrodepositing cobalt onto a substrate, wherein the electroplated cobalt deposit on the substrate surface comprises submicron recessed features and non-feature areas, wherein the variation in overburden thickness between the submicron recessed features and the non-feature areas is less than 50 nm, the method comprising: a) receiving the substrate in an electroplating chamber; b) immersing the substrate in a cobalt electrolyte, the cobalt electrolyte comprising: (1) a cobalt ion source; (2) Boric acid; (3) pH adjusters; and (4) an organic additive, wherein the organic additive comprises an alkoxylated propargyl alcohol or a reaction product of propargyl alcohol and a second component, wherein the second component comprises glycidol, propylene oxide, glycidol and propylene oxide, or propylene glycol and glycidol; wherein the cobalt electrolyte contains less than 1 ppm of chloride ions; wherein the cobalt electrolyte contains an amount of promoter that is undetectable by atomic absorption spectroscopy; and wherein the cobalt electrolyte contains less than 0.1 mg / L of divalent sulfur compounds; and c) electroplating cobalt into the submicron recessed features and onto the non-feature areas for a period of time and under conditions to achieve level, seamless, bottom-up filling in the submicron recessed features and plating on the non-feature areas, At 5 mA / cm 2 Up to 10mA / cm 2 The electroplated cobalt deposit exhibits a potentiodynamic hysteresis loop of less than 50 mV at high current density in a cyclic voltammetry scan at a current density within a range of 1 mA / cm 2 To less than 5mA / cm 2 At current densities within the range of 200 Å to 500 Å, the electroplated cobalt deposit exhibited a potentiodynamic hysteresis loop of less than 90 mV at low current densities in a cyclic voltammetry scan.

11. The method of claim 10, wherein the substrate has a cobalt seed layer disposed thereon, and the cobalt is electrodeposited onto the cobalt seed layer.

12. The method according to claim 10, wherein at 5 mA / cm 2 Up to 10mA / cm 2 At current densities within the range, the hysteresis loop of the potentiodynamic measurement was less than 30 mV at high current density in the cyclic voltammetry scan.

13. The method according to claim 12, wherein at 5 mA / cm 2 Up to 10mA / cm 2 At current densities within a range of 100 Å, the hysteresis loop of the potentiodynamic measurement was less than 10 mV at high current density in the cyclic voltammetry scan.

14. The method according to claim 10, wherein the current density of the hysteresis loop of the potentiodynamic measurement at high current density is 7.5 mA / cm 2 Up to 8.5mA / cm 2 within the range.

15. The method according to claim 10, wherein the current density of the hysteresis loop of the potentiodynamic measurement at low current density is 1.5 mA / cm 2 Up to 2.5mA / cm 2 within the range.

16. The method of claim 15, wherein: At 7.5 mA / cm 2 Up to 8.5mA / cm 2 At current densities within the range of 200 Å to 400 Å, the electroplated cobalt deposit exhibited a potentiodynamic hysteresis loop of less than 50 mV at high current density in the cyclic voltammetry scan.

17. The method of claim 10, wherein in the cyclic voltammetry scan, a forward scan represents non-feature area plating and a reverse scan represents feature area plating of the electroplated cobalt deposit.

18. The method of claim 10, wherein the cobalt electrolyte contains a depolarizer in an amount undetectable by atomic absorption spectroscopy.

19. The electroplated cobalt deposit of claim 1, wherein at 5 mA / cm 2 Up to 10mA / cm 2 The electroplated cobalt deposit exhibits a potentiodynamic hysteresis loop of less than 50 mV at high current density in a cyclic voltammetry scan at a current density within a range of 1 mA / cm 2 To less than 5mA / cm 2 At current densities within the range of 200 Å to 500 Å, the electroplated cobalt deposit exhibited a potentiodynamic hysteresis loop of less than 90 mV at low current densities in a cyclic voltammetry scan.

20. The electroplated cobalt deposit of claim 1 wherein the cobalt electrolyte consists of: (1) the cobalt ion source; (2) Boric acid; (3) the pH adjusting agent; and (4) The organic additive.

21. The method of claim 10, wherein at 5 mA / cm 2 Up to 10mA / cm 2 The electroplated cobalt deposit exhibits a potentiodynamic hysteresis loop of less than 50 mV at high current density in a cyclic voltammetry scan at a current density within a range of 1 mA / cm 2 To less than 5mA / cm 2 At current densities within the range of 200 Å to 500 Å, the electroplated cobalt deposit exhibited a potentiodynamic hysteresis loop of less than 90 mV at low current densities in a cyclic voltammetry scan.

22. The method of claim 10, wherein the cobalt electrolyte consists of: (1) the cobalt ion source; (2) Boric acid; (3) the pH adjusting agent; and (4) The organic additive.

Citation Information

Patent Citations

  • Superconformal electrodeposition of nickel iron and cobalt magnetic alloys

    US20090188805A1

  • Chemistry additives and process for cobalt film electrodeposition

    US20160273117A1

  • Superconformal filling composition and superconformally filling a recessed feature of an article

    US20190093248A1

  • Cobalt Filling of Interconnects

    US20190010624A1

  • Composition for cobalt plating comprising additive for void-free submicron feature filling

    WO2018015168A1